Social-Economic Aspects of the Regional Development Within Transform Economics - Regional Development in CR After Year 1990 - Iva Ritschelova; Jan Capek (European Regional Science Association (ERSA), 2006)
In the beginning of the transformation CR i.e. after year 1990, with started always expressive display in plant regional differences resulting from transformation process and transition Czech economies on market conditions. It was been and still is endeavour these disparities measurably equalize by regional policy state supports structurally depressed and economic weak regions. Regional disparity solving, and with it closely related well-balanced development regions, together constitute long - term process pointing to restraint disequilibrium in mutual relations among economic, environmental and social pillar sustainability and economic growth. For the safeguard development regions is therefore possibly to create conditions for lessening negative regional disparity and utilize inner potential particular regions at respected principles maintainable development Regional disparity and their solving will have out of doubt of principle impact on strategic orientation regional development CR in years 2007 - 2013. Authors in their article deal with identification disparity between eligible regions in CR, analyze development regional policy and her influence over elimination or deepening disparity over the last 15 years. Last but not least think of over strategy hers next development for the next period.
Keywords: 330